2011
DOI: 10.1080/02640414.2011.583672
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolism and performance improvement after two training programmes of sprint running differing in rest interval duration

Abstract: Repeated-sprint training often involves short sprints separated by inadequate recovery intervals. The effects of interval duration on metabolic and performance parameters are unclear. We compared the effects of two training programmes, differing in rest interval duration, on muscle (vastus lateralis) metabolism and sprint performance. Sixteen men trained three times a week for 8 weeks, each training session comprising 2-3 sets of two 80-m sprints. Sprints were separated by 10 s (n = 8) or 1 min (n = 8). Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…To assess the effect of exercise, we analyzed circulating irisin levels, before and after 2 or 3 sets of double sprints at first week and after 8 weeks of training, as described in the methods. As previously reported [15], analysis of muscle metabolite contents at week 1 showed that ATP levels were acutely decreased in response to exercise, along with decreased phospho-creatine levels (57.8±3.4 vs 31.8±3.5, mean±SE, p <0.01), and increased creatine, glucose, glucose-6-phosphate, glycerol-3-phosphate, fructose-6-phosphate (0.9±0.3 vs 1.9±0.3, p =0.02), and lactate (Fig. 6).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To assess the effect of exercise, we analyzed circulating irisin levels, before and after 2 or 3 sets of double sprints at first week and after 8 weeks of training, as described in the methods. As previously reported [15], analysis of muscle metabolite contents at week 1 showed that ATP levels were acutely decreased in response to exercise, along with decreased phospho-creatine levels (57.8±3.4 vs 31.8±3.5, mean±SE, p <0.01), and increased creatine, glucose, glucose-6-phosphate, glycerol-3-phosphate, fructose-6-phosphate (0.9±0.3 vs 1.9±0.3, p =0.02), and lactate (Fig. 6).…”
Section: Resultssupporting
confidence: 77%
“…Fifteen young, moderately trained, healthy males (age 20.5±1.5 years, BMI 21.9±1.6 kg/m 2 ) were assigned to an 8-week long training program involving 3 training sessions per week, as previously described [15]. Briefly, the training included 2 or 3 sets of runs on an indoor track with two 80-m sprint runs in each set.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we have assessed this hypothesis by employing two different training regimes, matched for total work, but which were associated with different changes in muscle lactate, PCr and hydrogen ion concentration. We show that reducing the length of the between‐interval recovery period, thereby producing a greater decrease in PCr content during each training session (Spencer et al 2006; Saraslanidis et al 2011), did not affect post‐training improvements in muscle PCr resynthesis postexercise. Thus, contrary to our hypothesis, training sessions that were accompanied by greater decreases in muscle PCr content did not result in significantly greater improvements in PCr resynthesis.…”
Section: Discussionmentioning
confidence: 78%
“…This investigation was originally designed to compare two repeated-sprint protocols [24]. The two training groups were apparently pooled for the retrospective analysis of circulating irisin.…”
Section: Discussionmentioning
confidence: 99%